Coastal oribatid mites (Acari) from New Zealand: new morphological, ecological, and developmental data - Pfingstl T; Minor M; Schäffer S; Shimano S (Informa UK Limited, trading as Taylor & Francis Group, 2023)
Three species of oribatid mites associated with tidal rocks and mangroves were collected on Waiheke Island, Hauraki Gulf, New Zealand. One of the species was a yet undescribed member of the genus Indopacifica, collected in algae growing on roots of green button mangrove Conocarpus erectus. Here, we provide a description of Indopacifica impedimenta sp. n, including its juvenile stages, and discuss its distribution and differences from congenerics. The second species collected was Fortuynia elamellata, which was found in algae growing on intertidal rocks. Here, we provide supplementary morphological data on adult and juvenile stages and discuss their distribution and ecology. The third species found was Sellnickia caudata, collected from the same mangrove as Indopacifica impedimenta n. sp. However, S. caudata occurred only on leaves and twigs of the mangrove plants, which are not regularly flooded. We provide supplementary morphological data and SEM images of adults and a description of juvenile stages for this species. We also discuss the family placement of Sellnickia and provide barcode sequences for all species studied herein.
Keywords: Auckland; mangrove; new species; Sellnickia; Indopacifica; Fortuynia